OZONIZED VEGETABLE OIL AND VETERINARY APPLICATION (Environmental Smoke, 2023)
Ozone (O3) is a molecule composed of three atoms of oxygen, very unstable, capable of reacting with various substances in the animal organism, giving rise to by-products that will participate in biochemical reactions. Under this reality, O3 has a broad mechanism of action and can be used in various pathologies of animals, being widely used in the treatment of wound healing. O3 is a substance found naturally in the Earth's atmosphere, however, for its therapeutic use, O3 is produced by a medical generator, which, through high-voltage-electrical-discharges, is capable of capturing medical oxygen from a cylinder and disintegrating it. it so that its molecules are reorganized in the form of ozone. Ozone therapy is considered an integrative therapy that is characterized by the application of a mixture of ozone gas and oxygen gas (O2), with a maximum of 5% O3 (CARNEIRO, 2023; DI FILIPPO et al., 2020). Because it has a broad mechanism of action, ozone therapy is effective in several animal pathologies. The purpose of repeated administration of ozone is to create resistance against oxidative stress by stimulating the antioxidant system, therefore, medicinal ozone is considered a prodrug, as its by-products are responsible for biological effects in the patient's body (DE OLIVEIRA et al., 2014; VASCONCELOS et al., 2022). Ozone in its medicinal use has established itself as a promising treatment and prophylaxis for several conditions, mainly due to its broad mechanism of action, with beneficial effects such as immunomodulatory, antimicrobial, anti-inflammatory, analgesic and healing. Allows penetration into the deep layers of the skin, increasing the supply of oxygen to the cells and strengthening the natural protective barrier. When using the product in oil, it should be used by applying a few drops to the affected areas of the skin several times a day and, in accordance with the guidance of the veterinarian, the treated area should be massaged (WILMINK; VAN WEEREN, 2004). The use of O3 is recommended when the patient has itching, skin inflammation, bacterial skin infections, fungal infections, hardened scar tissue, eczema, fissures, gingivitis and ear infections, always following the advice of the veterinarian. The application of ozone in the form of ozonated oil has been reported to be the most effective.